Correlation Between Sense of Humor and Burnout Among Primary Teacher in Jakarta - Yudhaningrum, Lupi; Hanifah, Aulia (Journal of Research and Measurement in Psychology: JPPP, 2019)
This study aims to determine the relationship between sense of humor with burnout on elementary school teachers in Jakarta. This research uses quantitative methods. The measuring instrument used to measure burnout is the Maslach Burnout Inventory EducatorsSurvey (MBI-ES). Sense of humor is measured by the Multidimensional Sense of Humor Scale (MSHS) by Thorson and Powell. The statistical method used to analyze the data of this study is the Spearman rank correlation. The results showed a significance value (p) of 0.010 (p <0.05). These results indicate that the hypothesis in this study is accepted that there is a significant relationship between sense of humor with burnout on elementary school teachers in East Jakarta. A negative sign on r count indicates the two variables have a non-directional relationship.